2019
DOI: 10.1111/jpm.12536
|View full text |Cite
|
Sign up to set email alerts
|

Nursing interventions in mental health and psychiatry: Content analysis of records from the nursing information systems in use in Portugal

Abstract: Accessible summary What is known about the subject? Planning and implementation of care are based on the selection and application of nursing interventions, which correspond to a key element in the nursing process. No information was found in the literature about which major nursing interventions are documented by nurses working in psychiatric wards. What the paper adds to existing knowledge? Despite the criteria applied to the intervention records' analysis may have led to the exclusion of certain impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 24 publications
(29 reference statements)
0
17
0
Order By: Relevance
“…Another limitation of this study was the absence of an external observer in the focus group meeting or videotaping, making it difficult to focus on participants' non‐verbal communication and interactions. We only conducted one focus group meeting that allowed data saturation (Goncalves et al 2019) but did not allow potential differences in the opinion of the participants to be identified over time. Another concern is related to the size of the focus group; if we conducted more meetings with smaller groups, the participants could have interacted more, perhaps leading to more in‐depth insights.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of this study was the absence of an external observer in the focus group meeting or videotaping, making it difficult to focus on participants' non‐verbal communication and interactions. We only conducted one focus group meeting that allowed data saturation (Goncalves et al 2019) but did not allow potential differences in the opinion of the participants to be identified over time. Another concern is related to the size of the focus group; if we conducted more meetings with smaller groups, the participants could have interacted more, perhaps leading to more in‐depth insights.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses consider it a complex system due to the difficulty in the recording process and data consultation. Other authors also reinforce the nurses' perception of the complexity in optimizing the SClínico program (Gonçalves et al, 2019;Oliveira et al, 2020;Vieira, 2018). The lack of standardization of records reported by the participants is a relevant limitation, because the use of a common language by nurses is crucial for the construction of formal knowledge (Gonçalves et al, 2019).…”
Section: Discussionmentioning
confidence: 69%
“…Other authors also reinforce the nurses' perception of the complexity in optimizing the SClínico program (Gonçalves et al, 2019;Oliveira et al, 2020;Vieira, 2018). The lack of standardization of records reported by the participants is a relevant limitation, because the use of a common language by nurses is crucial for the construction of formal knowledge (Gonçalves et al, 2019). Also, Oliveira et al (2020) highlighted the non-standardization of the care documentation process.…”
Section: Discussionmentioning
confidence: 69%
“…There has been some research on the use and relevance of SNTs in documentation in the psychiatric care but most of this has taken place in inpatient settings (e.g. Frauenfelder, van Achterberg, & Muller-Staub, 2018;Gonçalves, Sequeira, & Silva, 2019). Frauenfelder et al (2018) concluded that the NIC could be a suitable means to describe nursing care in the psychiatric inpatient setting but some interventions were found to be missing.…”
Section: What Does This Paper Contribute To the Wider Global Clinicalmentioning
confidence: 99%